Utilization of discarded crop straw to produce cellulose nanofibrils and their assemblies - Xiaran Miao; Jinyou Lin; Fenggang Bian (Journal of Bioresources and Bioproducts, 2020)
A tremendous amount of wheat straw (WS) has been generated by wheat crops every year, while only a small percentage is being used in applications, and most get burned on the field, causing a large amount of the exhaust gas that pollutes the environment. Herein, we report on the extraction of cellulose nanofibrils (CNF) from the alkali treated WS by a combination of 2,2,6,6-tetramethylpyperidine-1-oxyl (TEMPO)-oxidation and mechanical disintegration method. The crystalline structures, thermal properties, natural charge of the CNF were examined. The resultant nano-building blocks of the CNF was assembled into macroscopic cellulose materials, i.e., film, aerogel, and filament in this work. Furthermore, the morphologies and microstructues as well as other properties of these three kinds of the CNF assemblies were investigated. The obtained CNF and its assemblies showed a potential application in new materials areas. This work explored a new way to utilize the discarded WS instead of being burned.